Systemic Administration of a Brain Permeable Cdk5 Inhibitor Alters Neurobehavior - Umfress, Alan; Singh, Sarbjit; Ryan, Kevin J.; Chakraborti, Ayanabha; Plattner, Florian; Sonawane, Yogesh; Mallareddy, Jayapal Reddy; Acosta, Edward P.; Natarajan, Amarnath; Bibb, James A. (Frontiers in Pharmacology, 2022)
Cyclin dependent kinase 5 (Cdk5) is a crucial regulator of neuronal signal transduction. Cdk5 activity is implicated in various neuropsychiatric and neurodegenerative conditions such as stress, anxiety, depression, addiction, Alzheimer’s Disease, and Parkinson’s Disease. While constitutive Cdk5 knockout is perinatally lethal, conditional knockout mice display resilience to stress-induction, enhanced cognition, neuroprotection from stroke and head trauma, and ameliorated neurodegeneration. Thus, Cdk5 represents a prime target for treatment in a spectrum of neurological and neuropsychiatric conditions. While intracranial infusions or treatment of acutely dissected brain tissue with compounds that inhibit Cdk5 has allowed the study of kinase function and corroborated conditional knockout findings, potent brain-penetrant systemically deliverable Cdk5 inhibitors are extremely limited, and no Cdk5 inhibitor has been approved to treat any neuropsychiatric or degenerative diseases to date. Here, we screened aminopyrazole based analogs as potential Cdk5 inhibitors and identify a novel analog, 25-106, as a uniquely brain penetrant anti-Cdk5 drug. We characterize the pharmacokinetic and dynamic responses of 25-106 in mice and functionally validate the effects of Cdk5 inhibition on open field and tail-suspension behaviors. Altogether, 25-106 represents promising preclinical Cdk5 inhibitor that can be systemically administered with significant potential as a neurological/neuropsychiatric therapeutic.